PEMILIHAN TENAGA PENOLONG PERSALINAN DI DESA PANANCANGAN KECAMATAN CIBADAK KABUPATEN LEBAK PROVINSI BANTEN TAHUN 2017 - Andi Julia Rifiana; Wati Sufiawati (Universitas Nasional, 2018)
Background : Maternal deaths in Lebak district in 2016 were 38 cases from 21,292 live births. One cause is the help of birth by paraji (not nakes). Coverage coverage of Nakes at Puskesmas Cibadak in 2016 is only reached (71,6%) from target should (90%). While coverage in Panancangan village in 2016 (46.2%). Every year the delivery by health personnel in Panancangan village is always low and has never reached the target set. Objectives : Knowledge “Factors Associated With Selection of Labor Helpers in Panancangan Village, Cibadak Sub-district, Lebak District, Banten Province, 2017”. Methodology: using Cross Sectional design. The population of this study were all maternal mothers from October to December 2017, a total sample of 58 people. The research instrument used questionnaires. Results of analysis: Most (55.17%) of respondents chose labor on non-Nakes, (53.45%) respondents had good knowledge, 56.90% of housewives were close to Faskes, 58.62% health insurance, (53.45%) mother get support from husband / family, (55,17%) mother get support of health worker. Conclusions and suggestions: There is a relationship between the selection of auxiliary maternity helpers (p-palue 0,000), health insurance ownership (p value = 0,000; OR = 18,000), husband / family support (ppalue 0,000), and nakes support value = 0,000; OR = 42,857). While there is no significant relationship is the distance to health facilities (p value = 0.149). Suggestion: Health worker in Panancangan Village further increase counseling, increase pregnant mother class, socialization of P4K, partnership of midwife and paraji shaman to all deliveries safe and assisted by health personnel.